Comparative Analysis of Classical and Fractional-Order Models for Rabies Transmission - Jothi, Naresh Kumar; Muruganandham, Anusha; Deepa. S; Abraham, Neel Armstrong; Mattuvarkuzhali, Chandrasekaran (Trends in Immunotherapy, 2025)
Rabies is still a serious public health problem globally, especially where there is high dog-to-human contact and low vaccination coverage. In this paper, a fractional-order mathematical model is developed to explain the transmission dynamics of rabies in dogs and humans. The model is established by adopting the Caputo-Fabrizio fractional-order derivative (CFFROD), which suits the memory effects and non-locality properties of disease progression. The model has compartments for susceptible, exposed, infected, and recovered members of both species, as well as the viral load in the environment. Existence and uniqueness of solutions are proven via fixed-point theory to ensure mathematical consistency of the model. Numerical computations via the Adams-Bashforth method are performed to analyse the dynamics of the system for a range of fractional orders. Numerical computations provide evidence that fractional-order dynamics have a considerable impact on disease progression, ensuring the significance of memory in infectious disease modelling. Based on verified experimental data, a comparison between the fractional-order and classical models is presented. The results show that the fractional model provides greater insight into transmission and control timing patterns and best fits real-world data. This study supports the use of fractional modelling in the well-informed creation of successful rabies prevention initiatives and improved comprehension of disease dynamics.